2000
DOI: 10.1046/j.1432-1327.2000.01203.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a new class of oxylipins from N‐acyl(ethanol)amines by the lipoxygenase pathway

Abstract: N-Acylethanolamines (NAEs) constitute a new class of plant lipids and are thought to play a role in plant defense strategies against pathogens. In plant defense systems, oxylipins generated by the lipoxygenase pathway are important actors. To date, it is not known whether plants also use endogeneous oxylipins derived from NAEs in their defense reactions. We tested whether members of the NAE class can be converted by enzymes constituting this pathway, such as (soybean) lipoxygenase-1, (alfalfa) hydroperoxide ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
2

Year Published

2001
2001
2007
2007

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 37 publications
4
25
0
2
Order By: Relevance
“…28,[44][45][46][47][48] The spectra were in accordance with their chemical structures, as previously reported. 28,44,47,48 Each lipoxygenase was incubated with LEA, AEA (Cayman Chemicals), 3-AG, or 1-AG (1 U enzyme lipoxygenase per 3 µmol substrate) in 100 mM sodium borate buffer (pH 9 for soybean and pH 7 for barley grain). AEA was incubated with bovine polymorphonuclear leukocytes in phosphate-buffered saline (pH 7.4) to produce 12S-HAEA.…”
Section: Methodssupporting
confidence: 82%
“…28,[44][45][46][47][48] The spectra were in accordance with their chemical structures, as previously reported. 28,44,47,48 Each lipoxygenase was incubated with LEA, AEA (Cayman Chemicals), 3-AG, or 1-AG (1 U enzyme lipoxygenase per 3 µmol substrate) in 100 mM sodium borate buffer (pH 9 for soybean and pH 7 for barley grain). AEA was incubated with bovine polymorphonuclear leukocytes in phosphate-buffered saline (pH 7.4) to produce 12S-HAEA.…”
Section: Methodssupporting
confidence: 82%
“…4C). Predictable fragmentation ions including the molecular ion [M ϩ ] (m/z 573) were clearly identifiable, and spectra were comparable with those recorded in previous studies (Van der Stelt et al, 2000). Only ␣-ketols originating from 13-hydroperoxy NAE (18:2) were detected, indicating that imbibed cottonseeds contained both a 13-LOX and 13-AOS that metabolized NAE 18:2.…”
Section: Identification Of Nae Metabolites and Subcellular Distributisupporting
confidence: 76%
“…Recent evidence demonstrated that purified plant LOX, AOS, and HPO lyase could metabolize synthetic NAEs to generate novel oxylipins (Van der Stelt et al, 2000), raising the possibility that plants might catalyze these reactions in vivo. Here, we provide several lines of evidence that support this concept and highlight seed imbibition and germination as a period intensely involved in formation of these metabolites.…”
Section: Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of the specificity of the tea leave HPL, a 13-HPL, and our results indicated that the absolute position of the diene system in relation to the methylene end and not to the carboxyl end is an important factor for the substrate specificity. Nevertheless the carboxy group plays also a role, since methylation reduces often the activity whereas to some extent an acid-amine is a better substrate (van der Stelt et al, 2000;Kandzia et al, 2003). An influence of the pH is also discussed in respect to amount of carboxylate anion in relation to the undissociated carboxyl group.…”
Section: Discussionmentioning
confidence: 99%